Enfermedad renal crónica como factor de riesgo asociado a reingreso hospitalario temprano en pacientes adultos con insuficiencia cardiaca - Ávila Reyes, Pool Christopher (2019)
This research work is based on an analytical, observational, retrospective study of cases and controls, whose main objective is to identify if chronic kidney disease is a risk factor associated with early hospital readmission of adult patients with heart failure admitted to hospitalization of the Department of Medicine of the Trujillo Regional Teaching Hospital; considering a sample size in the case group of 35 patients and in the control group of 70 patients. As a conclusion of the work, chronic kidney disease will be demonstrated is a risk factor associated with early hospital readmission of adult patients with heart failure explained by the pathophysiology of cardiorenal syndrome..